Polycyclic Aromatic Hydrocarbons (PAHs) in paddy soil around Nam Son landfill area, Ha Noi, Viet Nam - Nguyen Thuy Ngoc,; Truong Thi Kim,; Nguyen Thi Quynh,; Phung Thi Vi,; Pham Hung Viet,; Duong Hong Anh, (Vietnam Journal of Science and Technology, 2023)
The paddy soils were collected in the rice growing fields and the uncultivated lands around the Nam Son domestic waste landfill in Hanoi. The average concentration of 16 US EPA priority PAHs in dry soil was 61.61 ng/g, with a range of 22.15-115.1 ng/g. The higher levels of PAHs in soil samples were observed in cultivated paddy fields near the landfill in comparison with the fields far from the landfill. On the other hand, there was no difference in PAHs levels in cultivated paddy fields near the landfill and along the irrigation water canal. Concentrations of 16 PAHs in paddy soils decreased in the order:  5 rings > 3 rings > 4 rings > 2 rings > 6 rings in this area. The PAH isomeric diagnostic ratios including Fluth/(Fluth+Pyr) ratio (Ave 0.43, a range of 0.17-0.61), BaA/(BaA+Chr) ratio (Ave 0.51, a range of 0.26-0.63), IcdP/(IcdP+BghiP) ratio (Ave 0.71, a range of 0.51-0.90) indicated that the potential main sources emitted PAHs in paddy soils from pyrogenic biomass combustion and coal burning. Compared with the risk threshold causing adverse impacts on the ecological environment from different countries in the world, concentrations of PAHs in the soil surrounding the Nam Son landfill area were still below the affected limit. However, environmental quality around the landfill area still needs to be regularly monitored to take timely measures to protect the environment in this area.